Perceived Attributes and E-Readiness of Extension Personnel to Use ICTs - , Akanksha Singh, Meera Singh (Archives of Current Research International, 2024)
ICT has become one of the cornerstones of modern culture. This is the age of the knowledge and communication technologies. Since we all agree that we are living in a digital age, the primary goal of the study is to examine how the Agriculture Coordinator and Kishan Salahkar using ICTs, for carrying out their job effectively and successfully, they must have high level of perception about perceived attributes of ICTs and e-readiness of ICTs. The Study carried out in Samastipur District of Bihar State. The interview schedule was the principal data collection method in the report, meanwhile frequency percentage and corelation coefficient are used as statistical tools for data analysis. On the basis of present study, it can be inferred that the respondent having very low level of e-readiness and also having high level of perceived attributes towards ICT. E-readiness is low because of lack of proper infrastructure facilities and training. To enhance the e-readiness and perceived attributes of ICT tools it is important to provide proper training and proper care and management of the use of ICTs.